Infectious disease in contact sports - Nash, E.; Anderson, B. J. (Sports Health: A Multidisciplinary Approach, 2019)
Context: Infections are common in contact sports. This review aims to describe the epidemiology, presenting signs and symptoms, treatment guidelines, and regulations for several common infections seen in contact sport athletes. The conditions discussed include bacterial skin infections, herpes simplex virus, molluscum contagiosum, common warts, tinea, scabies, head lice, conjunctivitis, human immunodeficiency virus, hepatitis C virus, and vaccine-preventable illnesses. Evidence Acquisition: Searches were performed across PubMed and MEDLINE research databases. In addition, general internet search engine results and reviews of reference lists of relevant papers were used to identify additional sources of evidence. Study Design: Clinical review. Level of Evidence: Level 4. Results: The most common infections seen in contact sport athletes include bacterial skin infections, herpes simplex virus, molluscum contagiosum, common warts, tinea, scabies, head lice, conjunctivitis, and vaccine-preventable illnesses. Other infections, including human immunodeficiency virus and hepatitis C, are uncommon but potentially life threatening. Conclusion: Infections are common in contact sport athletes. The provider who cares for these athletes should be aware of the most common infections and their appropriate management. Early diagnosis and appropriate clinical management are important for treating the infected athlete, minimizing risk of transmission, minimizing time lost from competition, and preventing large outbreaks.